Natural resource and environmental economics - Perman, Roger; Ma, Yue; McGilvray, James; Common, Michael (Harlow, England ; New York : Pearson Addison Wesley, 2003)
Provides a comprehensive and clear account of the application of economic analysis to environmental issues. This new edition has evolved with the times and been thoroughly updated to reflect recent developments in environmental issues and policies, such as forestry, biodiversity and pollution control. The early chapters explain the development and role of environmental economics before further chapters advance the student at a suitably challenging but achievable level.
Rev. ed. of: Natural resource and environmental economics / Roger Perman, Yue Ma, James McGilvray. 1996.
Includes bibliographical references (p. [671]-688) and indexes.
oif 08/08/16, ijb 09/04/2019
Loan
Keywords: Environmental economics; Natural resources - management; Sustainable development; Pollution